Evaluasi Penilaian Pelaksanaan Standar Manajemen Informasi dan Rekam Medis (MIRM) di Rumah Sakit - Elise Garmelia; Siswati Siswati; Sri Sugiarsi (Jurnal Rekam Medis dan Informasi Kesehatan, 2020)
According to the Ministry of Health that accreditation is a step to ensure hospitals to prioritize the service, safety and protection of the community. Hospitals as one of the health care institutions are required to provide quality services including in the implementation of medical records and health information that are in the standard of Information Management and Medical Records ( MIRM). The purpose of the research is to want to know the value of accreditation in standard MIRM instruments 8-15 namely medical record management from hospitals in 3 (three) regions in Indonesia. Quantitative descriptive research with a sample count of 14 hospitals. Data processing through scoring elements in SNARS 1.1 edition and processing with SPSS to analyze the value value relationship scoring elements of assessment in government and non-government hospitals. Analysis with Anova, independent simple test and multiple comparison. The result is that there is a significant difference of p=0.00 (p0.05) of scores or assessment elements between the 3 hospital areas, but there is no significant difference (o.788) p0.05) standard value (8-15) between government and non-government hospitals. The conclusion is the assessment standard of KARS that the fulfillment of MIRM (8-15) standards of both facilities, infrastructure and human resources has not been evenly distributed in every hospital in the 3 regions, while the use of every element of the assessment of MIRM standard ( 8-15) is standard for government hospitals of various classes as well as for non-government hospitals.  ABSTRAKMenurut Kementerian kesehatan bahwa  akreditasi adalah langkah untuk menjamin rumah sakit agar mengutamakan pelayanan, keselamatan dan perlindungan masyarakat. Rumah sakit sebagai salah satu institusi pelayanan kesehatan dituntut untuk memberikan pelayanan yang bermutu termasuk dalam penyelenggaraan rekam medis dan informasi kesehatan yang tersebut pada standard Manajemen Informasi dan Rekam Medis ( MIRM). Tujuan penelitian adalah ingin mengetahui nilai akreditasi pada instrumen MIRM standar 8-15 yakni manajemen rekam medis dari rumah sakit di 3 (tiga) wilayah di Indonesia. Penelitian deskriptif kuantitatif dengan jumlah sampel 14 rumah sakit. Pengolahan data melalui Skor setiap elemen penilaian yang ada pada buku SNARS edisi 1.1 dan pengolahan dengan SPSS untuk menganalisis hubungan nilai skor elemen penilaian di rumah sakit pemerintah dan non pemerintah. Analisis dengan Anova, uji independent simple test dan multiple comparison. Dengan hasil ada perbedaan signifikan p=0,00 (p0.05) skor atau elemen penilaian diantara 3 wilayah rumah sakit, namun tidak ada perbedaan (o,788) p0,05) yang signifikan nilai standard (8-15)  antara RS pemerintah dan non pemerintah. Kesimpulan adalah adanya standar penilaian dari KARS bahwa pemenuhan standar MIRM (8-15) baik sarana, prasarana dan SDM belum merata di setiap rumah sakit di 3 wilayah tersebut, sedangkan penggunaan setiap elemen penilaian dari standard MIRM ( 8-15) adalah baku bagi rumah sakit pemerintah berbagai kelas maupun untuk rumah sakit non pemerintah.